Loss of UBE3A from TH-expressing neurons suppresses GABA co-release and enhances VTA-NAc optical self-stimulation - Janet Berrios (Nature Portfolio, 2016)
Mesoaccumbal terminals within the VTA are known to co-release both GABA and dopamine, although the functional role of the former has yet to be determined. Here, the authors find that non-canonical GABA release is regulated by the E3-ubiquitin ligase, UBE3A, and enhances optogenetic self-stimulation.